Students’ Perception in Group Work Based on Gender Stereotypes in EFL Classroom - Shafira Shaberina; Esti Junining; Sri Wardani (Journal of English Education and Teaching, 2023)
Working in a group is the practice of cooperating with people who have a wide range of information, skills, and ideas. The importance of including group work activities in the school curriculum is becoming more widely recognized as a key component of a student-centered classroom. However, concerns about students’ attitudes toward choosing their desirable group members are affected by stereotypes of gender. This study used a mixed method to explore high school students in EFL Classroom at SMA N 1 Malang attitudes to determine desirable group members based on gender stereotypes. The results from thirty active students' questionnaires and interviews suggested that gender stereotypes were applied in choosing desirable group members especially in terms of communication, cooperation, and academic aspects. There are possibilities that the factors are not applicable to all students since everyone internalized gender stereotypes differently. This research suggests that teachers can let students choose their desirable group members based on their own preferences while also promoting gender bias-free teaching.